From environmental policy concepts to practicable tools: Knowledge creation and delegation in multilevel systems - Tosun, Jale; De Francesco, Fabrizio; Peters, B. Guy (Public administration, 2019)
The problem-solving capacity and problem-generating potential of multilevel systems entail the need for the delegation of authority. When the problem concerned is about how to put an abstract policy concept into a practicable policy tool, the choice of the respective delegation trajectory depends on the policy models or the policy-relevant knowledge that the respective political levels can supply. When regarding the European Union (EU) level as the starting point of knowledge creation and delegation trajectories, and concentrating on transaction costs, policy knowledge and models generated at the international level provide the most cost-effective solution. Only when the international level is not able to provide further policy knowledge and innovation does the EU delegate its definitional authority, first downward to the member states and then sideways to EU agencies. We illustrate the plausibility of our dynamic understanding of multilevel governance by using Environmental Policy Integration as an example.
First published: 11 August 2018
Gesehen am 22.10.2019
volume 97, issue 2 = Special issue: Symposia: Leadership for public value and integration, functional differentiation and problem-solving in multilevel governance